Isolation of actinomycin derivatives from diffusible pigment of Streptomyces sp. UKMCC_PT7 - Zainal Abidin, Zaima Azira; Ahmad, Asmat; Latip, Jalifah; Usup, Gires (2011)
This study was conducted to investigate the potential of marine actinomycetes isolated from Malaysian waters as producers of biologically active compounds. Streptomyces sp. UKMCC_PT7 was isolated from seawater collected in Pulau Tinggi, Johor. This bacterium was found to produce yellow diffusible pigment when growing on ISP3 medium. Preliminary screening showed that this yellow diffusible pigment possessed antibacterial properties. Ethyl acetate extraction was then carried out on agar containing the yellow pigment followed by separation of compounds using reverse-phase HPLC which led to the isolation of three metabolites; PT7_27, PT7_30 and PT7_31. All compounds exhibited UV maximal absorption at 433 nm with masses of 1272, 1269 and 1255 respectively. 1H and 13C/APT NMR data revealed that these compounds are actinomycin derivatives which consist of phenoxazinone chromophore with two lactonised pentapeptide attached via amide linkage. One of the compounds was established as Actinomycin D (C62H86N12O16), a widely used antitumor drug to treat Wilms’ tumor, Ewing’s sarcoma, rhabdomysarcoma and gestational trophoblastic disease. This study further demonstrated the unique capabilities of marine Streptomyces of producing more than one antibiotic simultaneously.